Gerakan Peduli Gizi: Pencegahan KEK pada Ibu Hamil Trimester I di Dusun Tundung, Desa Mantang, Lombok Tengah - Afriani, Nur; Ningsih, Nining Fatria; Wahyuni, Ervin Dini (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Chronic Energy Deficiency (CED) in pregnant women is a significant nutritional issue in Indonesia, including in Dusun Tundung, Desa Mantang, NTB, with a prevalence of 17% in the first trimester of pregnancy. Addressing CED through nutritional education and community empowerment is crucial to reduce the risk of pregnancy complications. The aim of this study is to improve the nutritional status of pregnant women and reduce the prevalence of CED through nutrition-based interventions. The method used is descriptive-qualitative with active community participation. The subjects of the study were 25 pregnant women at risk of CED. The results showed an average weight gain of 1.5-2 kg, an increase in the proportion of pregnant women with normal nutritional status from 40% to 68%, and a decrease in the prevalence of CED from 28% to 12%. Active family participation in preparing nutritious menus and the use of audiovisual educational media played a key role in the success of the program. In conclusion, community-based nutrition education programs are effective in improving the nutritional status of pregnant women and reducing the prevalence of CED in high-risk areas.